Impact of COVID-19 Pandemic on the Clinic Operations of Primary Care Physicians in Southern Negros Occidental - Terry-Sabay, Mylene P.; Guevarra, Joseph G. (Technium Social Sciences Journal, 2022)
The clinic operations of primary care physicians experienced an economic downturn affecting the delivery of healthcare services since the start of the pandemic. Thus, this research study determines the impact of the COVID-19 pandemic on the clinic operations of primary care physicians in Southern Negros Occidental in terms of business operation and marketing viability. The study also intended to discover the opportunities and challenges in primary care facility operations. The descriptive-comparative research design was used. Research findings show that the COVID-19 pandemic had a substantial impact on the clinic operations of primary care physicians. Moreover, age has a significant difference in the degree of impact of the COVID-19 pandemic on the clinic operations in both business operations and marketing viability. The study essentially addresses the limited data on the impact of the COVID-19 pandemic on the clinic operations. The medical society may utilize this study to look for strategies to minimize the impact of COVID-19 on primary care physicians and maintain the delivery of health services in a non-hospital-based setting. Keywords. Pandemic, clinic operations, primary care physicians, business operation, marketing viability, descriptive, Philippines